Competency-Based Training Effectiveness and Its Impact on Employee Productivity: Empirical Evidence from the Garment Industry in Purbalingga - Fatwa Zuhaena (ITB AAS Indonesia Surakarta, 2022)
The garment industry in Purbalingga Regency is a cornerstone of the local economy, yet persistent productivity gaps underscore the need for effective workforce development strategies. This study examines the effect of competency-based training effectiveness on employee productivity in garment companies in Purbalingga, with training motivation and training transfer as mediating variables. Grounded in Human Capital Theory (Becker, 1964) and the Kirkpatrick Training Evaluation Model (Kirkpatrick & Kirkpatrick, 2006), this study proposes that training effectiveness positively influences productivity directly and indirectly through two mediating pathways. A quantitative survey was conducted with 154 production employees from six garment companies. PLS-SEM analysis revealed that training effectiveness significantly affects training motivation (β = 0.398, p < 0.001), training transfer (β = 0.421, p < 0.001), and productivity directly (β = 0.287, p < 0.01). Both training motivation (β = 0.241, p < 0.01) and training transfer (β = 0.318, p < 0.001) significantly predict productivity. The model explains 62.4% of productivity variance (R² = 0.624), confirming the dual-mediation structure. Findings provide practical guidance for HR managers in designing impactful competency-based training programs. Keywords: competency-based training; training effectiveness; training motivation; training transfer; employee productivity; garment industry; PLS-SEM